Preparing for war the emergence of the modern U.S. Army, 1815-1917 - Clark, J. P. (Harvard University Press, 2017)
"Preparing for War examines historical changes in the ways American army officers have thought about and prepared for war. In 1815, most officers regarded innate "genius" as the paramount professional quality. So while the still new academy at West Point might impart useful technical knowledge of gunnery or engineering or drill manuals could standardize tactical commands and formations, officers felt that the most important elements of their trade were beyond the ability of formal institutions to instill or improve. By 1917, Progressive Era concepts of professionalism and organization had infiltrated the army, leading to a new way of preparing for war that included an expanded system of professional schools, realistic field training, and prescriptive tactical doctrine."...